Vapour–liquid–solid growth of monolayer MoS2 nanoribbons - Li, Shisheng; Lin, Yung-Chang; Zhao, Wen; Wu, Jing; Wang, Zhuo; Hu, Zehua; Shen, Youde; Tang, Dai-Ming; Wang, Junyong; Zhang, Qi; Zhu, Hai; Chu, Leiqiang; et al. (Nature materials, 2018)
Chemical vapour deposition of two-dimensional materials typically involves the conversion of vapour precursors to solid products in a vapour–solid–solid mode. Here, we report the vapour–liquid–solid growth of monolayer MoS 2 , yielding highly crystalline ribbons with a width of few tens to thousands of nanometres. This vapour–liquid–solid growth is triggered by the reaction between MoO 3 and NaCl, which results in the formation of molten Na–Mo–O droplets. These droplets mediate the growth of MoS 2 ribbons in the ‘crawling mode’ when saturated with sulfur. The locally well-defined orientations of the ribbons reveal the regular horizontal motion of the droplets during growth. Using atomic-resolution scanning transmission electron microscopy and second harmonic generation microscopy, we show that the ribbons are grown homoepitaxially on monolayer MoS 2 with predominantly 2H- or 3R-type stacking. Our findings highlight the prospects for the controlled growth of atomically thin nanostructure arrays for nanoelectronic devices and the development of unique mixed-dimensional structures. Monolayer MoS 2 can be laterally grown in the vapour–liquid–solid mode, forming highly crystalline nano- and microribbon structures.